Lithium-aluminum-silicon microcrystalline glass as well as preparation method and application thereof

By adjusting the composition and preparation process of lithium-aluminum silicon crystal crystallized glass, the problem of improving the performance of existing microcrystalline glass is solved, and lithium-aluminum silicon crystallized glass with high transmittance and high mechanical strength is prepared, meeting the requirements of mobile phone cover plates for high strength and good mechanical properties.

CN119551905APending Publication Date: 2025-03-04SHANDONG YIXIN PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411470821.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing high transmittance microcrystalline glass is difficult to further strengthen chemically, resulting in low fracture toughness, scratch resistance and drop resistance difficult to improve, and cannot meet the requirements of mobile phone covers for high strength and good mechanical properties.

Method used

By adjusting the composition design and preparation process of lithium-aluminum silicon microcrystalline glass, it specifically includes mixing oxides such as SiO2, Al2O3, Li2O, Na2O, B2O3, P2O5, ZrO2 and SnO2 in a specific proportion, melting, molding, annealing and ion exchange treatment, and preparing lithium-aluminum silicon microcrystalline glass with high transmittance, high strength and good mechanical properties.

Benefits of technology

It has achieved high transmittance (>92%) and high mechanical strength (Vickers hardness >630kgf/mm2, four-point bending strength >850MPa) of lithium aluminum silicon crystal glass in the visible light band, and at the same time it has improved its anti-scratch, drop and impact performance, meeting the high strength and good mechanical performance requirements of mobile phone covers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to lithium-aluminum-silicon microcrystalline glass and a preparation method and application thereof, and the lithium-aluminum-silicon microcrystalline glass comprises the following components in percentage by mass of oxides: 25 to 70 percent of SiO2, 35 to 24 percent of Al2O3, 7 to 15 percent of LiO2, 0 to 8 percent of Na2O, 30 to 7 percent of B2O3, 50 to 10 percent of P2O5, 20 to 5 percent of ZrO2 and 20 to 0.3 percent of SnO2. According to the lithium-aluminum-silicon microcrystalline glass obtained by adjusting the composition design and the preparation process of the lithium-aluminum-silicon microcrystalline glass, the transmittance of the lithium-aluminum-silicon microcrystalline glass at the visible light wave band with the wavelength of 560 nm and the thickness of 0.8 mm is greater than 92%, and the Vickers hardness is gt; 630 kgf / mm < 2 >, and four-point bending strength gt; the pressure is 850 MPa, and the anti-falling height is gt; the height of the impact-resistant falling ball is gt; the surface stress value is gt; the pressure is 875 MPa, and the stress layer depth is gt; the film has the advantages of high transmittance, high strength, good scratch resistance, good impact resistance and good drop resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass technology, and in particular to a lithium aluminum silicon glass-ceramic and a preparation method and application thereof. Background Art

[0002] With the booming development of portable mobile phone communications, the development of 5G communications has brought about major changes in the entire mobile phone accessories industry, especially the development and changes of mobile phone covers. Traditional mobile phone covers are mainly made of metal materials, but the wave absorption performance of metal materials is generally poor, and the shielding effect on mobile phone signals cannot meet the requirements of 5G communications. At the same time, consumers have higher and higher requirements for the appearance and texture of mobile phone covers. Glass and ceramic materials stand out under this trend due to their good wave absorption performance, unique appearance and good texture. Compared with ceramic materials, glass has the advantages of a wide range of raw material sources, low hardness, easy surface treatment, and richer colors, and has great market potential. However, traditional glass is brittle and prone to microcracks, making its actual mechanical strength 2 to 3 orders of magnitude lower than the theoretical mechanical strength. Therefore, improving glass strength has become a top priority in the development of mobile phone cover glass.

[0003] Glass-ceramics is also called glass-ceramics. It not only has the good light transmittance of glass, but also has the crystal structure and high strength of ceramic materials. It is a material with uniform and dense structure. Generally, certain nucleating substances in the glass can be added with nucleating agents or heat treated to make a large number of tiny crystals uniformly precipitate in the glass, forming a dense multiphase complex of microcrystalline phase and glass phase, thereby obtaining glass-ceramics. The microcrystals produced by nucleation can block or deflect the propagation path of microcracks, and improve the drop resistance, scratch resistance and impact resistance of the glass. Electronic products have high requirements for the transparency of cover glass, so the selected glass-ceramics must have a high optical transmittance. However, it is generally difficult to further chemically strengthen glass-ceramics with high transmittance, resulting in low fracture toughness, scratch resistance and drop resistance. It is difficult to further improve other properties.

[0004] Therefore, providing a microcrystalline glass with high transmittance and high strength, as well as good anti-scratch, anti-drop and impact resistance has become an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0005] The purpose of the present invention is to provide a lithium aluminum silicon glass-ceramic and a preparation method and application thereof, wherein the lithium aluminum silicon glass-ceramic has high transmittance, high strength, good anti-scratch, impact resistance and drop resistance.

[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a lithium aluminum silicon glass-ceramic, which comprises the following components, measured by mass percentage of oxides: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O0-8%, B2O30-7%, P2O50-10%, ZrO20-5%, and SnO20-0.3%.

[0007] Optionally, the lithium aluminum silicon glass-ceramics contains the following components, measured in percentage by mass of oxides: SiO2 59-68%, Al2O3 10-17%, Li2O 8-13%, Na2O 0-7%, B2O3 0-5%, P2O 50-6%, ZrO2 0-2%, and SnO2 0-0.1%.

[0008] Optionally, the mass ratio of the components of the lithium aluminum silicon glass-ceramics meets the following conditions: 10% <Li2O+Na2O<20%; (Li2O+Na2O+B2O3) / (SiO2+Al2O3)=0.2-0.3; ZrO2 / Li2O=0.03-0.06.

[0009] Optionally, when the thickness of the lithium aluminum silicon glass-ceramics is 0.8 mm, the transmittance in the visible light band of 560 nm is greater than 92%.

[0010] Optionally, the Vickers hardness of the lithium aluminum silicon glass-ceramics is greater than 630 kgf / mm 2 , four-point bending strength>850MPa, drop resistance height>185cm, impact resistance height>55cm.

[0011] Optionally, the surface stress value of the lithium aluminum silicon glass-ceramics is >875MPa, and the stress layer depth is >102μm.

[0012] A second aspect of the present invention provides a method for preparing lithium aluminum silicon glass-ceramics, the method comprising: The glass raw materials are mixed evenly, melted, formed and annealed, and then cut to obtain the basic glass; the glass raw materials contain the following components: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O 0-8%, B2O30-7%, P2O50-10%, ZrO20-5%, SnO20-0.3%; heat-treating the base glass to obtain glass-ceramics; The microcrystalline glass is pretreated and then subjected to a first ion exchange and a second ion exchange respectively to obtain lithium aluminum silicon microcrystalline glass.

[0013] Optionally, the melting temperature is 1600-1700°C, and the time is 3-6h; the annealing temperature is 550-600°C, and the time is 1-3h; the heat treatment temperature is 800-1000°C, and the time is 2-5h.

[0014] Optionally, the first ion exchange comprises: subjecting the pretreated glass-crystalline to a first ion exchange in a molten salt at a temperature of 400-420°C for 120-240 minutes, wherein the components of the molten salt comprise 75-80% Na2NO3 and 15-25% KNO3 by mass percentage; the second ion exchange comprises: subjecting the glass-crystalline after the first ion exchange to a second ion exchange in a molten salt at a temperature of 400-420°C for 120-240 minutes, wherein the components of the molten salt comprise 3-6% Na2NO3 and 92-96% KNO3 by mass percentage.

[0015] A third aspect of the present invention provides an electronic display device, characterized in that the electronic display device includes the lithium aluminum silicon glass-ceramics provided by the first aspect of the present invention.

[0016] Through the above technical scheme, the lithium aluminum silicon microcrystalline glass obtained by adjusting the composition design and preparation process of the lithium aluminum silicon microcrystalline glass in the present invention has a transmittance of more than 92% at a thickness of 0.8 mm in the visible light band of a wavelength of 560 nm, and a Vickers hardness of more than 630 kgf / mm 2 , four-point bending strength>850MPa, anti-drop height>185cm, anti-impact drop height>55cm, surface stress value>875MPa, stress layer depth>102μm, with high transmittance, high strength, good anti-scratch, impact and anti-drop performance.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] A first aspect of the present invention provides a lithium aluminum silicon glass-ceramic. The lithium aluminum silicon glass-ceramic comprises the following components, measured by mass percentage of oxides: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O 0-8%, B2O30-7%, P2O50-10%, ZrO20-5%, and SnO20-0.3%.

[0020] According to the present invention, optionally, the lithium aluminum silicon glass-ceramics contains the following components, measured in percentage by mass of oxides: SiO2 59-68%, Al2O3 10-17%, Li2O 8-13%, Na2O 0-7%, B2O3 0-5%, P2O 50-6%, ZrO2 0-2%, and SnO2 0-0.1%.

[0021] SiO2 is an essential component of the glass network structure, and its structural unit is [SiO4]. The higher its content, the better the chemical stability and mechanical strength. However, too high a content of SiO2 will cause quartz and quartz solid solution to appear during the microcrystallization of the glass, making melt forming difficult; therefore, the mass percentage of SiO2 in the present invention is controlled at 57-70%. Since SiO2 has the characteristic of significantly increasing the viscosity of the glass, it is not conducive to clarification and homogenization, and a defoaming agent such as SnO2 is often added; its introduction amount is controlled at 0-0.1%.

[0022] Al2O3 is a commonly used glass network intermediate, which can effectively connect [SiO4] with the network outer body, greatly improve the chemical stability of glass, reduce the tendency of glass crystallization, and at the same time improve the hardness, impact strength and elastic modulus of glass. However, the melting point of Al2O3 is as high as 2045°C, which increases the viscosity of glass. Based on the current industrial melting conditions and capabilities, the mass percentage of Al2O3 in the present invention is controlled at 5%-24%, which can take into account and coordinate the relevant physical and chemical properties and process properties such as glass melting temperature, melting quality, molding temperature, glass crystallization, glass mechanical strength and chemical stability.

[0023] R2O is the most important network exobody component and the material basis for glass to perform ion exchange. Alkali metal oxides (R2O) are mainly Li2O, Na2O and K2O, which can reduce the melting temperature of glass. Therefore, the mass percentage of R2O in the present invention is controlled at 10%-20%. The coexistence of Li2O and Na2O can promote the secondary strengthening of glass, making its ion exchange layer deeper and having better impact strength. Therefore, the mass percentage of Li2O in the present invention is controlled at 7-15%, and the mass percentage of Na2O is controlled at 0-8%.

[0024] B2O3 is an auxiliary component that forms the glass network structure, and has the functions of promoting glass melting, reducing viscosity, etc.; and helps to improve the scratch resistance of the glass surface. However, B2O3 can cause phase separation, and as the content increases, it will affect the transmittance of the crystallized glass. Therefore, the mass percentage of B2O3 in the present invention is controlled to be 0-7%.

[0025] P2O5 is also an auxiliary component of the glass network structure, and also has the characteristics of promoting glass melting and reducing viscosity. It exists as [PO4] in the glass structure. Unlike [SiO4], the phosphorus oxygen tetrahedron [PO4] has one phosphorus oxygen double bond (P=O), and the structural stability is not good. It must be combined with Al2O3 and B2O3 to form AlPO4 and BPO4 groups, and supplemented with a large amount of SiO2 to stabilize the glass structure. Therefore, the mass percentage of P2O5 in the present invention is controlled at 0-10%.

[0026] ZrO2 can prevent the exposure of alkali metal and alkaline earth metal ions, increase the elastic modulus, and help reduce the grain size during the crystallization process, thereby increasing the transmittance of the glass and improving the chemical stability of the glass; it can also increase the fracture toughness and bending strength of the glass. Therefore, the mass percentage of ZrO2 in the present invention is controlled to be 0-5%.

[0027] According to the present invention, optionally, the mass ratio of the components of the lithium aluminum silicon glass-ceramics satisfies the following conditions: 10% <Li2O+Na2O<20%; (Li2O+Na2O+B2O3) / (SiO2+Al2O3)=0.2-0.3; ZrO2 / Li2O=0.03-0.06.

[0028] According to the present invention, optionally, when the thickness of the lithium aluminum silicon glass-ceramics is 0.8 mm, the transmittance in the visible light band of 560 nm is greater than 92%.

[0029] According to the present invention, optionally, the Vickers hardness of the lithium aluminum silicon glass-ceramics is greater than 630 kgf / mm 2 , four-point bending strength>850MPa, drop resistance height>185cm, impact resistance height>55cm.

[0030] According to the present invention, optionally, the surface stress value of the lithium aluminum silicon glass-ceramics is >875MPa, and the stress layer depth is >102μm.

[0031] A second aspect of the present invention provides a method for preparing lithium aluminum silicon glass-ceramics, the method comprising: The glass raw materials are mixed evenly, melted, formed and annealed, and then cut to obtain the basic glass; the glass raw materials contain the following components: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O 0-8%, B2O30-7%, P2O50-10%, ZrO20-5%, SnO20-0.3%; heat-treating the base glass to obtain glass-ceramics; The microcrystalline glass is pretreated and then subjected to a first ion exchange and a second ion exchange respectively to obtain lithium aluminum silicon microcrystalline glass.

[0032] According to the present invention, optionally, the melting temperature is 1600-1700°C, and the time is 3-6h; the annealing temperature is 550-600°C, and the time is 1-3h; the heat treatment temperature is 800-1000°C, and the time is 2-5h.

[0033] According to the present invention, optionally, the first ion exchange includes: subjecting the pretreated glass-ceramics to a first ion exchange in a molten salt at 400-420°C for 120-240 minutes, wherein the components of the molten salt include 75-80% Na2NO3 and 15-25% KNO3 by mass percentage; the second ion exchange includes: subjecting the glass-ceramics after the first ion exchange to a second ion exchange in a molten salt at 400-420°C for 120-240 minutes, wherein the components of the molten salt include 3-6% Na2NO3 and 92-96% KNO3 by mass percentage. In the lithium aluminum silicon glass-ceramics system of the present invention, since the radius of the Li element is small, it is beneficial to the Li-Na ion exchange and provides conditions for the secondary ion exchange. The strength of the glass-ceramics after the secondary ion exchange is greatly improved, so that it can be better used in cover glass.

[0034] The third aspect of the present invention provides an electronic display device, which includes the lithium aluminum silicon glass-ceramics provided by the first aspect of the present invention. For example, the electronic display device can be the front cover and back cover of a smart phone.

[0035] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0036] Examples 1-8 S1: Weigh the glass raw materials according to the ratio. The glass raw materials and their ratios are shown in Table 1 and Table 3. After the glass raw materials are evenly mixed by ball milling, they are placed in a platinum crucible, placed in a high-temperature lifting furnace at 1650°C for 5 hours, and after the raw materials are completely melted, they are taken out and poured into a mold preheated to 500°C for molding, and annealed at 580°C for 2 hours; S2: The annealed glass is subjected to wire cutting, CNC engraving, processing, cleaning, edge grinding, and drying to obtain a base glass with a thickness of 0.8 mm; S3: heat treating the base glass at 900° C. for 3 h to obtain glass-ceramics; S4: preheating the glass-ceramics at 390°C for 90 minutes, and placing it in 80% Na2NO3+20% KNO3 molten salt at 410°C for a first ion exchange for 180 minutes; obtaining a lithium aluminum silicon glass-ceramics after a single strengthening; S5: Take out the microcrystalline glass after the first ion exchange and slowly cool it, clean the surface molten salt, put it into the preheating furnace again for preheating at 390℃ for 90min, and place it in 5%Na2NO3+95%KNO3 molten salt at 410℃ for the second ion exchange for 120min to obtain the lithium aluminum silicon microcrystalline glass after secondary strengthening.

[0037] Comparative Examples 1-3 S1: Weigh the glass raw materials according to the ratio. The glass raw materials and their ratios are shown in Table 1. After the glass raw materials are evenly mixed by ball milling, they are placed in a platinum crucible, placed in a high-temperature lifting furnace at 1650°C for 5 hours, and after the raw materials are completely melted, they are taken out and poured into a mold preheated to 500°C for molding, and annealed at 580°C for 2 hours. S2: The annealed glass is subjected to wire cutting, CNC engraving, processing, cleaning, edge grinding, and drying to obtain a base glass with a thickness of 0.8 mm; S3: heat treating the base glass at 900° C. for 3 h to obtain glass-ceramics; S4: Preheat the glass-ceramics at 390°C for 90 min, and place it in 5% Na2NO3+95% KNO3 molten salt for ion exchange at 410°C for 120 min to obtain strengthened lithium aluminum silicon glass-ceramics.

[0038] Test Examples 1-8 and Comparative Examples 1-3 The physical properties of the glass-ceramics prepared in the above Examples 1-8 and Comparative Examples 1-3 were measured, and the results are shown in Tables 1 to 4.

[0039] The symbols and measurement methods of physical properties are defined as follows: (1) Softening point and annealing point: Orton test is used.

[0040] (2) Transmittance: tested using a UV-visible spectrophotometer.

[0041] (3) Vickers hardness: measured using a HXD-3000 Vickers hardness tester with a loading force of 200 g and a loading time of 15 s.

[0042] (4) CS: Surface compressive stress is the abbreviation of Compressive Stress, which is tested using the FSM-6000LE surface stress meter produced by Orihara Industries, Ltd., Japan.

[0043] (5) DOL: Depth of Layer, tested using the FSM-6000LE surface stress meter from Orihara Industries, Ltd., Japan.

[0044] (6) Four-point bending strength (4PB): measured using a four-point bending strength measuring instrument.

[0045] (7) Impact resistance of falling ball height: measured by a falling ball impact tester. The specific test conditions are: a 60g steel ball is dropped from 15cm to 5cm at a time until cracks appear on the glass surface.

[0046] (8) Drop resistance (cm): Measured by a mobile phone controlled drop tester. The specific test conditions are: 180-grit sandpaper, 195g total weight, 60cm base height, 5cm increments, once per height, until broken.

[0047] Table 1.

[0048]

[0049] Table 2.

[0050]

[0051] Table 3.

[0052]

[0053] Table 4.

[0054]

[0055] The present invention can prepare lithium aluminum silicon microcrystalline glass by designing the components of microcrystalline glass and limiting the strengthening process parameters. The transmittance of 0.8mm thickness in the visible light band with a wavelength of 560nm is greater than 92%, and the Vickers hardness is greater than 630kgf / mm 2 , four-point bending strength>850MPa, anti-drop height>185cm, anti-impact drop height>55cm, surface stress value>875MPa, stress layer depth>102μm, with high transmittance, high strength, high hardness, high impact resistance and high drop resistance.

[0056] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0057] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0058] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A lithium aluminum silicon glass-ceramic, characterized in that: Measured in percentage by mass of oxides, the lithium aluminum silicon glass-ceramics comprises the following components: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O 0-8%, B2O3 0-7%, P2O5 0-10%, ZrO2 0-5%, and SnO2 0-0.3%.

2. The lithium aluminum silicon glass-ceramics according to claim 1, wherein: Measured in percentage by mass of oxides, the lithium aluminum silicon glass-ceramics comprises the following components: SiO2 59-68%, Al2O3 10-17%, Li2O 8-13%, Na2O 0-7%, B2O3 0-5%, P2O5 0-6%, ZrO2 0-2%, and SnO2 0-0.1%.

3. The lithium aluminum silicon glass-ceramics according to claim 1, wherein: The mass ratio of the components of the lithium aluminum silicon glass-ceramics meets the following conditions: 10% <Li2O+Na2O<20%; (Li2O+Na2O+B2O3) / (SiO2+Al2O3)=0.2-0.3; ZrO2 / Li2O=0.03-0.

06.

4. The lithium aluminum silicon glass-ceramics according to claim 1, wherein: When the thickness of the lithium aluminum silicon glass-ceramics is 0.8 mm, the transmittance in the visible light band of 560 nm is greater than 92%.

5. The lithium aluminum silicon glass-ceramics according to claim 1, wherein: The Vickers hardness of the lithium aluminum silicon glass-ceramics is>630kgf / mm 2 , four-point bending strength>850MPa, drop resistance height>185cm, impact resistance height>55cm.

6. The lithium aluminum silicon glass-ceramics according to claim 1, wherein: The surface stress value of the lithium aluminum silicon glass-ceramics is >875MPa, and the stress layer depth is >102μm.

7. A method for preparing lithium aluminum silicon glass-ceramics, characterized in that: The method includes: The glass raw materials are mixed evenly, melted, formed and annealed, and then cut to obtain the basic glass; the glass raw materials contain the following components: SiO2 57-70%, Al2O3 5-24%, Li2O 7-15%, Na2O 0-8%, B2O3 0-7%, P2O5 0-10%, ZrO2 0-5%, SnO2 0-0.3%; heat-treating the base glass to obtain glass-ceramics; The microcrystalline glass is pretreated and then subjected to a first ion exchange and a second ion exchange respectively to obtain lithium aluminum silicon microcrystalline glass.

8. The method according to claim 7, wherein: The melting temperature is 1600-1700°C, and the time is 3-6h; the annealing temperature is 550-600°C, and the time is 1-3h; the heat treatment temperature is 800-1000°C, and the time is 2-5h.

9. The method according to claim 7, wherein: The first ion exchange comprises: subjecting the pretreated glass-ceramics to a first ion exchange in a molten salt at 400-420° C. for 120-240 min, wherein the composition of the molten salt comprises 75-80% Na2NO3 and 15-25% KNO3 by mass percentage; The second ion exchange comprises: subjecting the microcrystalline glass after the first ion exchange to a second ion exchange in a molten salt at 400-420° C. for 120-240 min, wherein the components of the molten salt comprise 3-6% Na2NO3 and 92-96% KNO3 by mass percentage.

10. An electronic display device, characterized in that: The electronic display device comprises the lithium aluminum silicon glass-ceramics as described in any one of claims 1 to 6.